Classification of the type of eco-geological environment of a coal mine district: A case study of an ecologically fragile region in Western China - Yang, Zhi; Li, Wenping; Pei, Yabing; Qiao, Wei; Wu, Yanli (Journal of cleaner production, 2018)
Western China is characterized by abundant coal resources but it also faces the problems of poor water resources and fragile ecological environment, which have become more prominent due to the large-scale exploitation of coal resources in recent years. Shennan coal mine district is located at the border area between the Loess Plateau and Mu Us Desert of Northern Shaanxi province, which belongs to the typical arid and semi-arid ecologically fragile region of Western China, The geological features and ecological environmental characteristics of this district show wide variations with spatial distribution. However, intense coal mining activities will inevitably lead to further deterioration of the already fragile ecological and geological (eco-geological) environment, making recovery increasingly difficult. Therefore, investigating the different characteristics and classifying the types of the eco-geological environment are of great significance to in selecting appropriate mining methods, which would help in realizing coordinated exploitation of coal resources and environmental protection before coal exploitation. In this study, based on the remote sensing and geographic information system technology, Landsat8 remote sensing image, regional geological data, Digital Elevation Model (DEM), borehole data, hydrological data were analyzed. Furthermore, the eco-geological environment of the study area was classified into three types with the Normalized Difference Vegetation Index, surface elevation, terrain slope, surface lithology, geomorphic type, and hydrographic net are selected as the main control factors to classify eco-geological environment type. Each control factor was quantified using ArcGIS, with the aid of MATLAB 2014b as the computing platform, eco-geological environment of study area is classified into three types combining weighted fuzzy C-means (WFCM) clustering algorithm and the weight of each main control factor determined by fuzzy Delphi analytic hierarchy process (FDAHP) method. Finally, the classification of the eco-geological environment was verified through a field survey of the Hongliulin coal mine, and the results showed high accuracy. •The type of eco-geological environment of a coal mine district in Western China is classified into 3 types.•The sensitivity of different types of eco-geological environment to mining activities is different.•The type classification may lay the foundation to sustainable development of coal resources in arid and semi-arid regions.